Iterative Simulation-Based Design of a Multi Input Controller for a Hybrid Renewable Energy System - Abdullahi, Inusa (Universiti Malaysia Sarawak (UNIMAS), 2021)
Sustainable energy supply is a priority need for the socioeconomic and entrepreneurial development of communities in remote areas. Especially, in a developing country like Malaysia, providing sustainable energy to these areas has become a challenging task for the government. From past records, a micro-hydro plant hardly works for more than one year continuously without having problems like stalling or breakdowns due to ecological/technical problems. Generators' fuel has been very expensive and further away from remote villagers. The enhancement of single-source standalone renewable energy to the hybrid structure will provide an alternative power supply as standby to the consumer load. The one important component to this method is the automated control units that could monitor all resources’ conditions and decide which source of power supply is on standby. The Micro-Hydro is the main source and solar photovoltaic with the other energy resources are at standby. With that, in this study, a design of an iterative sequential controller for multiple inputs, single-output power system was considered and proposed. Micro-hydro and solar photovoltaic renewable energy, energy storage, and Utility grid are used as alternative standby resources, determined by priority. The projected concept is an interactive user-friendly, flexible, visually analytical for remote standalone hybrid renewable energy station regulators. The design applies an algorithm to implement an object-oriented finite-state machines model constructed from Simulink to obtain a multiple-input single-output profile. The model-depicted curves of sequential transition trajectory contour, logic truth table, etc. in the practical selection for project work. The hybrid design of the controller improved the standalone renewable energy system sustainability and alleviate other challenges at a lower cost.